Development and functional characterization of extrahepatic cholangiocyte lines from normal rats. Issue 11 (November 2015) - Venter, Julie; Francis, Heather; Meng, Fanyin; DeMorrow, Sharon; Kennedy, Lindsey; Standeford, Holly; Hargrove, Laura; Wu, Nan; Wan, Ying; Frampton, Gabriel; McMillin, Matthew; Marzioni, Marco; et al.
Abstract Background Since limited in vitro tools exist for evaluating the pathophysiology of extrahepatic bile ducts, we aim to develop an extrahepatic cholangiocyte culture system from normal rats. Methods Extrahepatic ducts were dissected from rats, cut in half length-wise and cultured on collagen-I coated plates. Transepithelial electrical resistance was measured. At ∼85% confluence, in extrahepatic cholangiocytes we measured: (i) cell size and distribution, and expression for cytokeratin-19, secretin, secretin receptor and somatostatin receptor type II (SSTR2), cystic fibrosis transmembrane conductance regulator (CFTR), chloride bicarbonate anion exchanger 2 (AE2), vascular endothelial growth factor-A (VEGF-A) and nerve growth factor (NGF); and (ii) the effect of secretin and/or somatostatin on 3′-5′-cyclic adenosine monophosphate (cAMP) levels and proliferation. Results Cytokeratin-positive extrahepatic cholangiocytes were cultured for 6 passages to form a cell monolayer. Cholangiocytes proliferated to confluence over a 2-week period. The size of extrahepatic cholangiocytes averaged ∼16 μm. Extrahepatic ducts and cholangiocytes were positive for secretin, secretin receptor and SSTR2, CFTR, AE2, VEGF-A and NGF. In extrahepatic cholangiocyte cultures, secretin increased cAMP (prevented by somatostatin), chloride efflux and proliferation. Conclusions Extrahepatic cholangiocyte cultures may be important for studying diseases targeting extrahepatic cholangiocytes such as biliary atresia.